Reconsidering technical education in Saxony: human resource development for an industrialised society and brain drain - Seiji Horii (Cogent Arts & Humanities)
This study critically examines the impact of technical education institutions on the early industrialisation of 19th-century Saxony, highlighting the role of the Technischen Bildungsanstalt zu Dresden in equipping the Saxon region with skilled workers, in line with post-Seven Years’ War recovery efforts: Rétablissement. Since the 18th century, educational entities have been established to cater to the technological needs driven by economic and societal imperatives. The study scrutinises the TBA curricula and explores the evolution of course offerings, in alignment with societal requirements. While TBA alumni significantly contributed to Saxony’s machine and railway sectors, the number of skilled workers produced was not sufficient to fully sustain industrialisation. Although many graduates secured employment within the manufacturing sector and contributed as educators, the emigration of professionals to less competitive markets abroad indicated brain drain. Notably, some graduates sought opportunities outside Saxony in German-speaking and non-German-speaking regions, indicating a trend of highly educated workforce emigration. This study reveals that TBA’s influence on Saxony’s industrial progress was substantial and that it contributed to the global technical labour market, underscoring the broader international relevance of technical education. This study re-evaluates the regional and international significance of technical education, offering new insights from a historical perspective.